Integrasi Technology Readiness dan Technology Acceptance Model Terhadap Kesiapan Pengguna Enterprise Resource Planning (ERP) pada Industri Pengolahan Kelapa Organik - Afiana, Fiby Nur; Rifai, Zanuar; Frilisia, Willy Ardo (Diponegoro University, 2024)
The manufacturing engineering technology that is widely used to integrate activities, financial management, production, and projects into human resource management is Enterprise Resource Planning. One of them is Odoo which is utilized by an organic coconut processing company in Banyumas Regency. Investment in technology often raises pros and cons in a company, where technology investment cannot immediately provide benefits. So the attitude of Human Resources and the level of user readiness for the Adoo application really needs to be studied. The TRAM (Technology Readiness and Acceptance and Odel) method is a combination of the concepts of the Technology Readiness and Technology Acceptance Model, used to determine the effect of user readiness on technology acceptance in a company with the addition of one variable, namely perceived enjoyment. The results obtained by the five hypotheses are stated to have a positive and significant effect, while the two hypotheses are stated to have a negative and insignificant effect. Technology Readiness has a positive and significant effect on Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, and Intention to use Odoo while Perceived Usefulness and Perceived Ease of Use have a negative and insignificant effect on Intention to use Odoo. Perceived Enjoyment has a positive and significant effect on the Intention to use Odoo and is a factor that quite influences the readiness and acceptance of new technology. The results of the research can be used by companies to weigh and decide how the company is going towards technology. Considering that the cost of adopting technology is sufficient and significant, it cannot immediately provide benefits to the company, but the benefits can be felt several years later.